Answer:
<h3>6</h3>
Step-by-step explanation:
Given the expression g(c) = 6c/2, we are to find the value when c = 2
Substitute c = 2 into the expression
g(2) = 6(2)/2
g(2) = 12/2
g(2) = 6
<em>Hence the result when c = 2 is 6</em>
Seven hundred and fifty one thousand
I hope this helps
Step-by-step explanation:
= -4 ÷ ( 1/3 × (7 - 1/2) ) + 3
= -4 ÷ ( 1/3 × 13/2 ) + 3
= -4 ÷ 13/6 + 3
= -4 × 6/13 + 3
= -24/13 + 3
= -24/13 + 39/13
= 15/13
The values cannot be labeled as dependent or independent without a givin equation